Biological biogas upgrading capacity of a hydrogenotrophic community in a trickle-bed reactor. (15th October 2016) - Rachbauer, Lydia; Voitl, Gregor; Bochmann, Günther; Fuchs, Werner
Graphical abstract: Highlights: Data on long term operation of a system supplied with real biogas are presented. Ex-situ biological methanation is feasible for biogas upgrading. Gas quality obtained complies with strictest direct grid injection criteria. Biomethane can act as flexible storage for renewable surplus electricity. Abstract: The current study reports on biological biogas upgrading by means of hydrogen addition to obtain biomethane. A mesophilic (37 °C) 0.058 m 3 trickle-bed reactor with an immobilized hydrogenotrophic enrichment culture was operated for a period of 8 months using a substrate mix of molecular hydrogen (H2 ) and biogas (36–42% CO2 ). Complete CO2 conversion (> 96%) was achieved up to a H2 loading rate of 6.5 mn 3  H2 /m 3 reactor vol.  × d, corresponding to 2.3 h gas retention time. The optimum H2 /CO2 ratio was determined to be between 3.67 and 4.15. CH4 concentrations above 96% were achieved with less than 0.1% residual H2 . This gas quality complies even with tightest standards for grid injection without the need for additional CO2 removal. If less rigid standards must be fulfilled H2 loading rates can be almost doubled (10.95 versus 6.5 mn 3  H2 /m 3 reactor vol.  × d) making the process even more attractive. At this H2 loading the achieved methane productivity was 2.52 mn 3  CH4 /m 3 reactor vol.  × d. In terms of biogas this corresponds to an upgrading capacity of 6.9 mn 3  biogas/m 3 reactor vol.  × d. The conducted experiments demonstrate that biological methanation in an external reactor is well feasible for biogas upgrading under the prerequisite that an adequate H2 source is available.